Robust lateral control of long-combination vehicles under moments of inertia and tyre cornering stiffness uncertainties. Issue 12 (2nd December 2019) - Sadeghi Kati, Maliheh; Köroğlu, Hakan; Fredriksson, Jonas
ABSTRACT: A robust steering-based controller synthesis is presented for an A-double combination vehicle with a steerable dolly. The controller ensures robust stability and performance in the face of uncertainties in the cornering stiffness of the tyres and the moments of inertia of the semitrailers, which are treated as time-varying and time-invariant parameters respectively. A descriptor-type representation of the system is employed since a standard state-space model depends rationally on the moments of inertia. The controller synthesis is formulated as an H ∞ -type static output feedback, which uses information from only one articulation angle. The driver steering input is also used by including a static feed-forward. The proposed synthesis method is based on linear matrix inequality (LMI) optimisation. The controller is verified based on the simulation results obtained from both (approximate) linear and (high-fidelity) nonlinear vehicle models. The results indicate significant improvement in the high-speed lateral performance of the A-double in the presence of parametric uncertainties.